Husserl on Ethical Renewal and Philosophical Rationality: Intercultural Reflection - Yu, Chung-Chi (Investigaciones Fenomenológicas, 2012)
In the Kaizo articles, written between 1922 and 1924, Husserl drew on the intercultural relationship between Europe and non-Europe. The viewpoints he held in these articles do not deviate much from that in the Vienna lecture 1935, which is later included in Crisis. It is in the latter that Husserl delineates systematically what he thinks of the idea of Europe and what makes Europe different from the other parts of the world. Notably, these viewpoints were already disclosed in the Kaizo articles, though in very different contexts. As is well known, the background of Crisis is the concern about the modern science which deviates more and more from the concrete lifeworld, whereas the Kaizo articles focus mainly on the ethical problems. Nevertheless both of them touch on the cultural as well as intercultural problematic, that Husserl deals with more and more intensively in his late philosophy. My essay will discuss the following questions: On what grounds does Husserl think that the philosophical rationality of Europe deserves being recommended to other cultures? How does he come to this conclusion in his discourse on ethics? In order to come to terms with these questions I will unfold my essay in three steps: first, I will sketch how Husserl understands ethics; secondly, explain the connection between ethics and philosophical rationality, and thirdly how these ethical thoughts have intercultural relevance.